Implementasi maqamat tasawuf dan etika bisnis Islam terhadap transaksi jual beli pada sales seragam Sabhara (Samapta Bhayangkara) - Imro'ah, Wulidatul (Maliki Interdisciplinary Journal, 2023)
The implementation of maqamat tasawwuf and Islamic business ethics in buying and selling transactions at Sabhara uniform sales (Samapta Bhayangkara) refers to the application of Islamic spiritual and business principles in every aspect of the transaction. Maqamat Sufism, which refers to the spiritual level in Sufism, can be applied by ensuring the principles of Islamic business ethics in carrying out buying and selling transactions. Sales must be able to create an ethical business environment in accordance with Islamic values, and provide positive benefits for all parties involved in buying and selling transactions. The purpose of this research is to find out the implementation of tasawwuf maqamat in the form of zuhud, wara', and qana'ah, as well as Islamic business ethics in the form of the principles of honesty/truth, the principle of justice/balance, and the principle of responsibility in buying and selling transactions at sabhara uniform sales (samapta bhayangkara ), and to find out the perceptions of sabhara uniform sales (samapta bhayangkara) regarding the maqamat of Sufism and Islamic business ethics. This research is a qualitative research with a case study method. The data collection technique used was fact findings or data in the field in the form of interviews with a sabhara uniform salesperson (samapta bhayangkara), as well as collecting a lot of information from literary sources including various book sources, previous research, and scientific journals. The results showed that the maqamat of Sufism in the form of zuhud, wara', and qana'ah, as well as Islamic business ethics in the form of the principles of honesty/truth, the principles of justice/balance, and the principle of responsibility have been implemented in buying and selling transactions at sabhara uniform sales (samapta bhayangkara), so that the maqamat of Sufism and Islamic business ethics are very important to be implemented in the activities of daily life, especially in the economic field, namely in buying and selling transactions.